The Adaptive Approach in Digital Transformation of Primary Education: Implementation of Digitalization in Elementary Schools in Maluku - Syauta, Daverychio Dhaniel Hendrik; Titaley, Elsina; Pelupessy, P. J. (Baileo: Jurnal Sosial Humaniora, 2024)
This study investigates the adaptive strategies in the digital transformation of elementary education in Maluku, an eastern Indonesian region facing geographical and infrastructural constraints. The research aims to analyze how elementary schools respond to the imperative of educational digitalization in the disruptive era. Using a qualitative method with a descriptive approach, data were collected through in-depth interviews, observation, and literature review. The findings reveal that although digital transformation is necessary and inevitable, it is hindered by limited technological infrastructure, uneven teacher readiness, and resistance to change. Nonetheless, some schools demonstrate adaptive innovations by utilizing available technology and engaging local communities in the learning process. These practices highlight that digital transformation is not solely dependent on infrastructure but also on the mental resilience and willingness of educators to embrace change. The novelty of this study lies in its contextual focus on remote island education and its emphasis on local adaptation as a key factor in successful digital implementation. The study recommends targeted teacher training, consistent mentoring, and improved access to digital resources to support sustainable transformation. This research contributes to social sciences and humanities by offering new insights into digital education strategies in marginalized and geographically isolated regions.